Predicting Covid-19 Preventive Behaviors Based on Health Belief Model: An Internet-Based Study in Mazandaran Province, Iran - Maryam Khazaee-Pool; Shokoh Shahrousvand; Seyed Abolhassan Naghibi (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Coronavirus disease (COVID-19) is an infectious disease caused by the new corona virus. The disease has led to high death toll and extensive damage throughout the world. The aim of this study was to determine the predictors of COVID-19 preventive behaviors in Iranian population based on the Health Belief Model. Materials and methods: A descriptive-analytical cross-sectional study was carried out in 400 individuals older than 18 years of age in Mazandaran Province, Iran 2020. They were selected using convenience sampling in social networks. Data were collected by a researcher-made scale based on Health Belief Model. Data analysis was done applying Pearson correlation coefficient and linear regression. Results: There were significant positive correlations between preventive behaviors of COVID-19 and perceived susceptibility (r=0.2, P=0.000), perceived benefits (r=0.127, P=0.011), perceived barriers (r=0.189, P=0.000), and perceived self-efficacy (r=0.302, P=0.000). The Health Belief Model constructs predicted 26% of variance for preventive behaviors of COVID-19, among which, perceived self-efficacy (β=0.220) was the most powerful predictor. Conclusion: This study confirmed the predictive role of self-efficacy in COVID-19 preventive behaviors according to the Health Belief Model. Thus, providing ways to increase self-efficacy such as verbal persuasion, increasing awareness about people abilities, and providing them with suitable models could promote preventive behaviors toward COVID-19.